Reaping the Returns of a Runaway Economy - Stan Pannier (Tijdschrift voor Sociale en Economische Geschiedenis)
Over the past few decades, economic and maritime historians have shown growing interest in the wages earned by regular seamen in merchant shipping. Due to a lack of sources, however, the composition and size of these earnings remain an elusive topic, as are the economic, demographic, and political processes that shaped them. In this article, I conduct a micro-history of seamen’s earnings in Ostend’s merchant marine during the early 1780s, a period of commercial uptick in the principal port town of the Austrian Netherlands. I show how a confluence of wartime circumstances and domestic economic policies led to extraordinary wage levels. From a micro point of view, I show how individual seamen reaped the returns of this runaway port economy by successfully wrangling over wages and harnessing the mobility of their profession, both between and within ports. As such, this article provides a perspective on wage-formation from a neutral and small maritime power, as well as a novel history from below of Ostend’s boom years.